Seroprevalence and risk factors of brucellosis in goats in selected states in Nigeria and the public health implications (2014)
Available reports on brucellosis in Nigeria are largely confined to cattle while it is believed that other ruminants like sheep and goats are equally exposed to the disease. To have an insight into the role of goats in the epidemiology of brucellosis in Nigeria, we conducted a cross-sectional study between June 2011 and May 2013 to determine the seroprevalence of brucellosis in goats in some selected states in Nigeria. Serum samples were collected from goats at different locations and tested for antibodies to Brucella spp using the Rose Bengal Test (RBT), samples positive by RBT were further subjected to Competitive Enzyme Linked Immunosorbent Assay (cELISA). Data collected to determine risk factors were also analysed using chi-square and logistics regression statistics. Out of a total of 2827 samples tested from the different states (Benue = 331; Borno =195; Oyo = 2155; Sokoto = 146), we recorded an overall seroprevalence of 2.83% (Benue = 17.30%; Borno = 2.05%; Oyo = 0.60% and Sokoto = 0.00%) by RBT. The cELISA further supported 9.45% (7/74) of the total RBT positive samples. Logistic regression analysis showed that the location (p = 0.004) and source (p < 0.0001); are probable risk factors to be considered in the epidemiology of brucellosis with sex (p = 0.179); age (p = 0.791) and breed (p = 0.369) not playing any major role. Our findings reveal a relatively low seroprevalence of brucellosis among goats screened except for Benue State. Since most of the goats sampled in the present study were from the abattoirs, further farm level investigations are required to determine the role of goats in the epidemiology of brucellosis in Nigeria since they share common environment with sheep and cattle that are natural hosts of Brucella species which are of major public health threat.